2008
DOI: 10.1097/rli.0b013e31817e9b0b
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of Coiled Cerebral Aneurysms: Comparison of Three-Dimensional Time-of-Flight Magnetic Resonance Angiography at 3 Tesla With Three-Dimensional Time-of-Flight Magnetic Resonance Angiography and Contrast-Enhanced Magnetic Resonance Angiography at 1.5 Tesla

Abstract: TOF-MRA follow-up of coiled aneurysms is better at 3 T than at 1.5 T; nevertheless, greater definition of residual patency is achieved with ultrafast CE-MRA at 1.5 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
(22 reference statements)
1
24
0
1
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18][19]24 In summary, some of these studies showed results similar to those in our current study, and some showed the superior performance of MRA relative to DSA compared with that in our current study, though some of these differences are very likely related to the differences in the aneurysm occlusion scales used. Conflicting conclusions regarding the performance of MRA relative to DSA and of the performance of various MRA techniques relative to each other certainly still exist, however.…”
Section: Discussionsupporting
confidence: 35%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17][18][19]24 In summary, some of these studies showed results similar to those in our current study, and some showed the superior performance of MRA relative to DSA compared with that in our current study, though some of these differences are very likely related to the differences in the aneurysm occlusion scales used. Conflicting conclusions regarding the performance of MRA relative to DSA and of the performance of various MRA techniques relative to each other certainly still exist, however.…”
Section: Discussionsupporting
confidence: 35%
“…There remains ambiguity over the overall performance of MRA relative to DSA in the depiction of coiled aneurysm remnants and in the relative performance of TOF-MRA, bolus gadolinium CE-MRA, and MRA performed at the field strengths of 1.5 T versus at 3T, with different groups reporting conflicting results. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] We wished to prospectively study the performance of MRA relative to DSA for the clinical indication of the follow-up of coiled intracranial aneurysms, and more specifically, we wished to study the relative performance of the 2 major types of MRA at 2 popular main magnetic field strengths, 1.5 and 3T. We present the results of a prospective clinical trial comparing the accuracies of 4 different MRA techniques, TOF and CE-MRA both at 1.5T and at 3T, by using DSA as the standard of reference in the follow-up of coiled intracranial aneurysms.…”
mentioning
confidence: 99%
“…5 Nevertheless, some authors 2 have not found significant improvements with the use of CE-MRA compared with unenhanced TOF acquisitions. In our personal experience, 4 we found better evidence of small remnants (Raymond type 1) after CE-MRA and better delineation of the recanalization in larger residual portions (Raymond type 2).…”
mentioning
confidence: 83%
“…[1][2][3][4] The use of high resolution steady-state acquisition with a blood-pool agent is similar to that of extracellular contrast media enhanced TOF-MRA, in which veins also enhance and overlap the arterial structures, in some cases giving false-positive images of aneurysm recanalization. With bloodpool agents, the risk of complete enhancement of both arteries and veins is more likely, potentially leading to more falsepositive findings.…”
mentioning
confidence: 99%
“…10,13 Although some authors have not used contrast material, [10][11][12][13][14][16][17][18][19][20]23,29,33,35 some have used contrast-enhanced MRA (CE-MRA) to increase signal intensity in residual pouches. 7,15,17,21,22,[24][25][26][27][28]31,32,34 The added value of arterial contrast enhancement in the follow-up of coiled aneurysms, however, remains controversial, and venous enhancement often degrades image quality. 15,17,25,31,32 Blood-pool contrast media (BPCM) remain in the intravascular space for a longer time, therefore permitting both first-pass and delayed steady-state imaging.…”
mentioning
confidence: 99%